Effect of emotion dysregulation on alcohol and marijuana outcomes via internal motives: A longitudinal study - Michelini, Yanina Noelia (2023)
Introduction: Previous studies showed difficulties in emotion regulation is related to self-medicate use of alcohol and marijuana (i.e., substance use to alleviate emotional distress or to increase pleasant emotions). However, longitudinal evidence on these relationships is still scarce. Aim: The present study aimed to longitudinally examine the effect of emotion dysregulation on alcohol and marijuana outcomes (i.e., use and problems) via internal motives (i.e., enhancement and coping) in Argentinian college emerging adults (i.e., aged 18 to 30). Method: A sample of 498 participants completed two online surveys (six months between each) assessing last-month alcohol use and negative consequences, last-three-month marijuana use and associated problems, internal motives (i.e., coping and enhancement) to use alcohol or marijuana and difficulties in negative emotion regulation. Of these participants, 468 (72% women; Mage= 23.62 SD= 3.04) reported last-month alcohol use, while 241 (63% women; Mage= 23.78 SD= 2.92) reported last-three-month marijuana use. Results: Coping motives mediated the associations of emotion dysregulation with typical week quantity of alcohol use and with negative consequences. Instead, the relationship between emotion dysregulation and marijuana frequency use was mediated by enhancement motives. Discussion: Findings support and extend previous cross-sectional evidence showing that, in students with problems to regulate emotions, motivation to cope with negative affect and to intensify pleasurable sensations could contribute to problematic use of alcohol and marijuana use, respectively. They also provide the basis for developing research that determines whether interventions focused on managing the negative emotional experience are useful in preventing increasing in alcohol and marijuana consumption.